Vanadium-doped lithium manganese iron phosphate positive electrode material and preparation method and application thereof
Through vanadium doping and secondary hydrothermal method, the problem of structural distortion of lithium manganese iron phosphate positive electrode material during charging and discharge is solved, and the capacity, magnification and cyclic stability are improved.
Patent Information
- Application Number
- CN202411811036.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-07
AI Technical Summary
Lithium manganese iron phosphate positive electrode material is prone to crystal geometric distortion during charging and discharging, resulting in a decrease in cyclic stability and discharge capacity.
The vanadium doping is performed by primary hydrothermal method, and the short nanorod particles of lithium manganese iron phosphate are grown in a direction by secondary hydrothermal method to form nanoparticles with a length less than 100nm and a width less than 20nm, improving the morphology and structure of the material.
The capacity, rate performance and cycle stability of the material are significantly improved, and the negative impact of V3+ on cycle performance is mitigated.
Smart Images

Figure CN119569020A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and more specifically, relates to a vanadium-doped lithium manganese iron phosphate positive electrode material and a preparation method and application thereof. Background Art
[0002] In recent years, new energy technologies, especially rechargeable batteries, have made great progress. Compared with traditional zinc-manganese dry batteries and lead-acid batteries, lithium-ion batteries are widely used in commercial energy storage devices due to their high energy transmission efficiency, high voltage and long cycle life. The lithium manganese iron phosphate positive electrode material studied in this invention is a common positive electrode material for lithium-ion batteries and has a higher voltage platform. 2+ Due to the influence of the charge and discharge, the geometric structure of the crystal is easily distorted, resulting in a certain degree of reduction in cycle stability and discharge capacity. To address this problem, doping, surface coating modification, material morphology control and other methods are often used to control the morphology and structure of the material to improve the electrochemical performance of the material during the charge and discharge process.
[0003] At present, element doping is mostly used to increase material lattice defects and improve its electrochemical performance by regulating the material structure. 3+ 、Co 2+ 、Zn 2+ , Cu 2+ It is more common to dope Mn / Fe with transition metal ions, which effectively weakens the interaction between Li-O chemical bonds, increases the bond lengths of Li-O and OO bonds, and expands the Li + Diffusion channels enhance Li + The migration rate is increased, and some transition metal ions replace the Mn sites, which improves the manganese dissolution during the charge and discharge process to a certain extent. However, it is difficult to significantly improve the performance of lithium manganese iron phosphate positive electrode materials by only doping elements.
[0004] The present invention finds that the lithium manganese iron phosphate positive electrode material obtained by vanadium doping by a primary hydrothermal method has a significantly improved discharge specific capacity during the charge and discharge process, but the capacity decay rate is relatively fast, and the cycle performance is significantly affected. It is accidentally found that the secondary hydrothermal method causes the short nanorod particles of the lithium manganese iron phosphate to grow in a directional manner into nanoparticles with a length of less than 100nm and a width of less than 20nm, thereby reducing the Li + The diffusion size in the
[010] direction shortens the Li + The diffusion path of lithium manganese iron phosphate can obtain a more uniform morphology and larger specific surface area of lithium manganese iron phosphate positive electrode material, which can effectively reduce the capacity decay of the material during the charge and discharge process, improve the cycle performance, and reduce V 3+ The impact on the cycle performance of lithium manganese iron phosphate can effectively solve the technical problems existing in primary hydrothermal vanadium doping.
[0005] In summary, the present invention adopts a hydrothermal method to prepare vanadium in-situ doped lithium manganese iron phosphate positive electrode material, which effectively reduces the V 3+ The difficulty of entering the material lattice. The secondary hydrothermal method is used to further control the directional growth of short manganese iron phosphate nanorod particles, and the manganese iron phosphate lithium positive electrode material with smaller particle size, more regular and uniform morphology is obtained compared with the direct preparation by the hydrothermal method. At the same time, the surface carbon coating is performed to improve the conductivity of the positive electrode material. By transferring metal ions (V 3+ ) doping and secondary hydrothermal morphology control are used to modify the morphology and structure of the material. Mn / Fe positions are substituted in the material to weaken the Li-O chemical bond and expand the Li + The diffusion channel reduces the dissolution of manganese in the cycle process, and the morphology is nanorod-like particles with a length of less than 100nm and a width of less than 20nm, which improves the electrochemical performance of the material in terms of capacity, rate and cycle stability. Summary of the invention
[0006] The present invention increases the Li content of lithium manganese iron phosphate positive electrode material by element doping. + diffusion channel, reducing the Mn 2+ The influence of dissolution on the cyclic stability of the material is studied. At the same time, the secondary hydrothermal preparation method is combined to achieve control of the material morphology and particle size, which significantly improves the material's capacity, rate performance and cyclic stability, and achieves multi-faceted improvements in electrochemical performance.
[0007] The primary purpose of the present invention is to provide V 3+ The preparation method of doped lithium manganese iron phosphate is as follows: a soluble reducing agent, an iron source, a manganese source, ammonium metavanadate, a lithium source and a phosphorus source are uniformly mixed, a hydrothermal reaction is performed to obtain a lithium manganese iron phosphate precursor, and then a secondary hydrothermal reaction is performed, and then mixed with a carbon source and calcined to obtain vanadium-doped lithium manganese iron phosphate nanoparticles.
[0008] Furthermore, the hydrothermal synthesis temperature is 140°C-200°C, preferably 140°C-180°C, and the time is 4h-12h, preferably 4h-10h; the secondary hydrothermal synthesis temperature is 140°C-200°C, preferably 140°C-180°C, and the time is 0.5h-4h, preferably 0.5h-2h; the calcination temperature is 400°C-800°C, preferably 500°C-700°C, and the time is 6h-12h, preferably 6h-10h.
[0009] The soluble reducing agent of the present invention includes at least one of glucose, sucrose and vitamin C; the iron source includes at least one of ferrous oxalate and ferrous sulfate; the manganese source includes at least one of manganese phosphate and manganese sulfate. The lithium source includes at least one of lithium hydroxide, lithium phosphate, lithium dihydrogen phosphate or dilithium hydrogen phosphate; the phosphorus source includes at least one of phosphoric acid, lithium phosphate, lithium dihydrogen phosphate or dilithium hydrogen phosphate; and the carbon source includes at least one of ascorbic acid, glucose and sucrose.
[0010] The molecular formula of the vanadium-doped lithium manganese iron phosphate positive electrode material of the present invention is Li(Mn 0.5 Fe 0.5 ) 1-x V x PO4; the mass of the carbon source added C accounts for 2wt%-10wt% of the vanadium-doped lithium manganese iron phosphate positive electrode material, preferably 2wt%-5wt%; the doping amount x of V is in the range of 0.1%-1%, preferably 0.25%-0.5%, which is converted into a mass percentage in the range of 0.08wt%-0.8wt%, preferably in the range of 0.2wt%-0.4wt%.
[0011] The hydrothermal solution medium of the present invention is ethylene glycol, dimethyl sulfoxide or a mixed solution of ethylene glycol and water.
[0012] Furthermore, the solvent of the hydrothermal system includes a mixed solution of ethylene glycol and water, wherein the ratio of ethylene glycol to water is in the range of 1:3-3:1, and the preferred range is 1:2-2:1; the products after the two hydrothermal reactions are dried in a vacuum drying oven, the drying temperature range is 60°C-120°C, the preferred range is 80°C-100°C, and the drying time range is 12h-24h, and the preferred range is 18h-24h.
[0013] Furthermore, the product washing reagent includes deionized water, methanol, ethanol, preferably water and ethanol. The washed product needs to be filtered and then vacuum dried. The drying temperature is 60°C-100°C and the drying time is 12h-24h.
[0014] The short nanorod particles of lithium manganese iron phosphate prepared by the invention are directionally grown into nanoparticles with a length of less than 100nm and a width of less than 20nm.
[0015] The second aspect of the present invention aims to provide a vanadium-doped lithium manganese iron phosphate positive electrode material prepared by the method described.
[0016] The third aspect of the present invention aims to provide an application of the vanadium-doped lithium manganese iron phosphate positive electrode material for preparing a battery positive electrode, especially a lithium ion battery positive electrode.
[0017] The fourth aspect of the present invention aims to provide a battery or lithium-ion battery positive electrode, which is prepared from the vanadium-doped lithium manganese iron phosphate positive electrode material.
[0018] Furthermore, the present invention adopts the following steps to prepare the positive electrode sheet of a lithium ion battery:
[0019] 1) Lithium manganese iron phosphate positive electrode material (Li(Mn 0.5 Fe 0.5 ) 1-x V x PO4), acetylene black or Super P and polyvinylidene fluoride (PVDF), mix them evenly in a ratio of 7:2:1, make them into a paste with N-methylpyrrolidone and evenly apply it on the aluminum foil.
[0020] 2) Dry in a vacuum oven at 100°C for 12 hours.
[0021] The test method for the electrochemical performance of the electrode material is as follows:
[0022] 1) The simulated battery adopts a button cell CR2016 system, the electrolyte is a LiFP6 system, the lithium sheet is used as the negative electrode, and the separator is a PP / PE separator;
[0023] 2) The reversible capacity and cycle performance of the electrode material are tested and analyzed by constant current charge and discharge. The charge and discharge regime is as follows: voltage range: 2.8~4.2V; the number of cycles is generally 1~200 times.
[0024] Due to the implementation of the above technical solution, the present invention has the following advantages compared with the prior art:
[0025] The present invention prepares vanadium-doped and modified lithium manganese iron phosphate positive electrode material (Li(Mn 0.5 Fe 0.5 ) 1-x V x PO4), using the preferential binding of vanadium to phosphate, the hydrothermally synthesized lithium manganese iron phosphate material is modified by iron / manganese doping, which improves the manganese dissolution of the material during the charge and discharge process and weakens the interaction between Li-O chemical bonds. At the same time, the directional growth of the material is controlled by secondary hydrothermal method to reduce Li + The diffusion size in the
[010] direction shortens the Li + The diffusion path of the electrode is shortened, thereby providing a faster electrochemical response for the electrode reaction and improving the electrochemical performance of the lithium manganese iron phosphate cathode material from both structural and morphological aspects. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the XRD distribution diagram of lithium manganese iron phosphate (LMFP) prepared in Comparative Example 1.
[0027] Figure 2 Preparation of vanadium-doped lithium manganese iron phosphate material (Li(Mn 0.5 Fe 0.5 ) 1-x V x PO4)’s XRD profile.
[0028] Figure 3 The lithium manganese iron phosphate (Li(Mn 0.5 Fe 0.5 ) 1-x V x PO4) electron microscope image;
[0029] Figure 3 a is the pure phase of lithium manganese iron phosphate prepared in comparative example 1, which has not been subjected to secondary hydrothermal treatment, and the material agglomerates seriously and is uneven in size, with a particle size of about 200nm-300nm. Figure 3 b is the vanadium-doped lithium manganese iron phosphate positive electrode material prepared in Example 3, Figure 3 (c) is the vanadium-doped lithium manganese iron phosphate prepared in Comparative Example 2, and its morphology is similar to that of Comparative Example 1.
[0030] Figure 4 The lithium manganese iron phosphate (Li(Mn 0.5 Fe 0.5 ) 1-x V x PO4) at 0.2C electrochemical cycling performance curve.
[0031] Figure 5 The lithium manganese iron phosphate (Li(Mn 0.5 Fe 0.5 ) 1-x V x PO4) electrochemical cycle performance curve at 1C; Figure 5 a is the electrochemical performance cycle curve of Example 1, Figure 5 b is the electrochemical performance cycle curve of Example 2, Figure 5 c is the electrochemical performance cycle curve of Example 3, Figure 5 d is the electrochemical performance cycle curve of Example 4.
[0032] Figure 6 The lithium manganese iron phosphate (Li(Mn 0.5 Fe 0.5 ) 1-x V x PO4) rate performance curve. DETAILED DESCRIPTION
[0033] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0034] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0035] Example 1
[0036] A method for preparing vanadium-doped lithium manganese iron phosphate positive electrode material
[0037] Step 1: Dissolve 2.77 g of ferrous sulfate, 1.69 g of manganese sulfate, 0.2 g of ascorbic acid, and 0.0058 g of ammonium metavanadate in 35 mL of a mixture of ethylene glycol and water, and stir thoroughly to dissolve to form solution A;
[0038] Step 2: Dissolve 1.436 g of lithium hydroxide in a mixture of 25 mL of ethylene glycol and water, and stir thoroughly to dissolve to form solution B;
[0039] Step 3: uniformly drip solution A into phosphoric acid to form a manganese-iron mixed solution;
[0040] Step 4: uniformly drip solution B into the manganese-iron mixture, stir for 30 min, transfer to a 100 mL hydrothermal kettle, and heat at 180 ° C for 8 h. After the reaction is complete, centrifuge the solution, wash with water and ethanol for 3 times, and dry at 80 ° C for 24 h.
[0041] Step 5: Disperse the material evenly in a mixture of ethylene glycol and water, transfer to a 100 mL hydrothermal kettle, heat at 180°C, and heat for 0.5 h. After the reaction is complete, centrifuge the solution, wash with water and ethanol three times, and dry at 80°C for 24 h.
[0042] Step 5: After being mixed evenly with the carbon source, calcined at 650°C for 6h in a low temperature tube furnace to obtain Li(Mn 0.5 Fe 0.5 ) 1-x V x PO4 (x=0.25%) positive electrode material.
[0043] To verify its electrochemical performance: Li(Mn 0.5 Fe 0.5 ) 1-x V x PO4 (x = 0.25%), binder and conductive agent are dissolved in N-methylpyrrolidone to prepare slurry, which is then coated on aluminum foil and vacuum dried to assemble lithium-ion batteries as electrode materials. The electrochemical performance is tested and the first cycle capacity at 0.2C is close to 140mAh·g -1Above, the first cycle capacity is 122mAh·g at 1C -1 After 100 cycles, the capacity is 112.26 mAh g -1 , the capacity retention rate is 92%.
[0044] Example 2
[0045] Compared with Example 1, most of the methods are the same, except that the amount of ammonium metavanadate added is changed in this example.
[0046] 0.0070g of ammonium metavanadate was mixed with a manganese source, an iron source, a lithium source, and a phosphorus source, and then subjected to a hydrothermal reaction. The obtained product was dried and calcined in a low-temperature tube furnace under Ar2 conditions to obtain a lithium manganese iron phosphate material Li (Mn) with a vanadium doping content of 0.3%. 0.5 Fe 0.5 ) 1-x V x PO4(x=0.3%).
[0047] To verify its electrochemical performance: Li(Mn 0.5 Fe 0.5 ) 1-x V x PO4 (x = 0.3%), a binder and a conductive agent were dissolved in N-methylpyrrolidone to prepare a slurry, which was coated on aluminum foil and vacuum dried to assemble a lithium-ion battery as an electrode material. The electrochemical performance was tested and the first cycle capacity at 0.2C was 148.63 mAh g -1 The first cycle capacity at 1C is 136.1mAh·g -1 After 100 cycles, the capacity is 125 mAh g -1 The capacity retention rate is 91.8%.
[0048] Example 3
[0049] Compared with Example 1, most of the methods are the same, except that the amount of ammonium metavanadate added is changed in this example.
[0050] 0.0082g of ammonium metavanadate was mixed with a manganese source, an iron source, a lithium source, and a phosphorus source, and then subjected to a hydrothermal reaction. The obtained product was dried and calcined in a low-temperature tube furnace under Ar2 conditions to obtain a lithium manganese iron phosphate material Li (Mn) with a vanadium doping content of 0.3%. 0.5 Fe 0.5 ) 1-x V x PO4(x=0.35%).
[0051] To verify its electrochemical performance: Li(Mn 0.5 Fe 0.5 ) 1-x V xPO4 (x = 0.35%), a binder and a conductive agent were dissolved in N-methylpyrrolidone to prepare a slurry, which was coated on aluminum foil and vacuum dried to assemble a lithium-ion battery as an electrode material. The electrochemical performance was tested and the first cycle capacity at 0.2C was 151.36 mAh g -1 The first cycle capacity at 1C is 144 mAh g -1 The discharge capacity after 100 cycles is 137.1 mAh g -1 The capacity retention rate is 95.2%, with high discharge specific capacity and good cycle performance.
[0052] Example 4
[0053] Compared with Example 1, most of the methods are the same, except that the amount of ammonium metavanadate added is changed in this example.
[0054] 0.0116 g of ammonium metavanadate was mixed with a manganese source, an iron source, a lithium source, and a phosphorus source, and then subjected to a hydrothermal reaction. The obtained product was dried and calcined in a low-temperature tube furnace under Ar2 conditions to obtain a lithium manganese iron phosphate material Li (Mn) with a vanadium doping content of 0.3%. 0.5 Fe 0.5 ) 1-x V x PO4(x=0.5%).
[0055] To verify its electrochemical performance: Li(Mn 0.5 Fe 0.5 ) 1-x V x PO4 (x = 0.5%), binder and conductive agent were dissolved in N-methylpyrrolidone to prepare slurry, coated on aluminum foil, and vacuum dried to assemble lithium-ion batteries as electrode materials. The electrochemical performance was tested and the first cycle capacity at 0.2C was close to 140mAh·g -1 The first cycle discharge capacity at 1C is 132.3 mAh g -1 After 100 cycles, the capacity decayed to 128.46 mAh g -1 , the retention rate is 97%.
[0056] Comparative Example 1
[0057] Compared with Example 1, most of the aspects are the same. In this comparative example, pure-phase lithium iron manganese phosphate material is prepared without adding ammonium metavanadate as a vanadium source, and the lithium iron manganese phosphate is not subjected to secondary hydrothermal treatment.
[0058] The electrochemical performance of pure phase lithium manganese iron phosphate material is as follows: 0.2C first cycle capacity is 134mAh·g -1 , close to 140mAh·g -1The capacity retention rate is 95%, and the maximum capacity at 1C is 106.94mAh·g -1 , the capacity retention rate is 95% after 100 cycles.
[0059] Comparative Example 2
[0060] Compared with Example 1, most of the aspects are the same. In this comparative example, a hydrothermal vanadium-doped lithium manganese iron phosphate positive electrode material is prepared once, and no secondary hydrothermal treatment is performed on it.
[0061] The electrochemical performance of the single hydrothermal vanadium doping is as follows: 0.2C first cycle capacity is 164 mAh g -1 The first cycle capacity at 1C is 135.34mAh·g -1 After 100 cycles, the capacity decayed to 122.49 mAh g -1 The capacity retention rate is 90.5%. Compared with comparative example 1, although the discharge specific capacity is significantly improved, the cycle performance is significantly reduced.
[0062] The lithium-ion batteries obtained in the above examples were analyzed, and the specific results are as follows:
[0063] Figure 1 The lithium iron manganese phosphate positive electrode material is prepared by a single hydrothermal method in Comparative Example 1 of the present invention. The relevant diffraction peaks in its diffraction spectrum can be matched one by one with the standard card (00-011-0456Li(Fe,Mn)PO4), indicating that the present invention adopts a hydrothermal method to synthesize a lithium iron manganese phosphate positive electrode material with good crystallinity, high purity and complete crystal form.
[0064] Figure 2 The lithium manganese iron phosphate (Li(Mn 0.5 Fe 0.5 ) 1-x V x The XRD spectrum of the lithium manganese iron phosphate (LMFP) material prepared in Comparative Example 1 matches the relevant diffraction peaks of the lithium manganese iron phosphate positive electrode material. V doping does not have a significant effect on the crystal form and structure of the lithium manganese iron phosphate positive electrode material. Example 1-Example 4 When the doping content is relatively low, x=0.25%, the XRD diffraction pattern of the material is basically similar to the XRD diffraction spectrum of LMFP, indicating that when the doping amount is low, its effect on the material is weak, but with the increase of the doping amount, when it reaches 0.3%, it is found that part of its main peak has shifted to a small angle, and the shift amplitude of the main peak to a small angle is gradually increased as the doping amount is further increased (when x=0.5%, the test peaks of the material near 20°, 40°, and 50° all shift to the left). From the perspective of ionic radius, it is mainly due to the Mn 2+ The ionic radius is V 3+ The ionic radius is Due to the addition of V3+ The ionic radius of the substituted Fe 2+ The ionic radius is large, the lattice constant is increased, and the XRD test peak shifts to a small angle, which also proves that vanadium has successfully entered the lattice of the lithium manganese iron phosphate positive electrode material, increased the lattice defects inside the material, weakened the strength of the Li-O bond, and achieved an increase in the lithium ion diffusion rate, which significantly improved the electrochemical performance of the material.
[0065] Figure 3 (a) is the pure phase of lithium manganese iron phosphate prepared in Comparative Example 1, which was not subjected to secondary hydrothermal treatment. The material agglomerates more severely and is uneven in size, with a particle size of about 200nm-300nm. Figure 3 (b) is the vanadium-doped lithium manganese iron phosphate positive electrode material prepared in Example 3. It is found that its morphology is also short nanorod-like. Compared with the lithium manganese iron phosphate that has not undergone secondary hydrothermal treatment, its morphology is more uniform. The size and length of the nanorods are basically the same, and the particle size is within 100 nm. Figure 3 (c) is the vanadium-doped lithium manganese iron phosphate prepared in comparative example 2, and its morphology is similar to that of comparative example 1. The agglomeration of the material into secondary particles with larger particle size and irregular morphology shows that vanadium doping has no significant effect on the morphology of the material. The relatively uniform morphology of the short nanorod primary particles in Example 3 is mainly caused by the secondary hydrothermal step. Therefore, the secondary hydrothermal method in the present invention plays an important role in regulating the morphology of the lithium manganese iron phosphate positive electrode material, and affects the nucleation and growth of the material during the crystallization process, and finally obtains a lithium manganese iron phosphate positive electrode material with smaller particle size, more uniformity, higher crystallinity and better electrochemical performance.
[0066] Figure 4 The lithium manganese iron phosphate (Li(Mn 0.5 Fe 0.5 ) 1-x V x PO4) at 0.2C, the electrochemical performance of Example 1 (x = 0.25%) is relatively poor; the first cycle discharge specific capacity of Example 2 (x = 0.3%) at 0.2C is 148.63 mAh·g -1 , Li(Mn 0.5 Fe 0.5 ) 1-x V x PO4 first cycle capacity at 0.2C: 151.36 mAh g -1 , as V 3+ As the doping amount increases, the electrochemical performance of Example 4 (x=0.5%) decreases to a certain extent.
[0067] Figure 5 The lithium manganese iron phosphate (Li(Mn0.5 Fe 0.5 ) 1-x V x PO4) electrochemical cycle performance curve at 1C. The electrochemical performance of Example 1 (x = 0.25%) is relatively poor. The first cycle capacity of Example 2 (x = 0.3%) at 1C is 136.1 mAh·g -1 After 100 cycles, the capacity is 125 mAh g -1 The capacity retention rate is 91.8%; the Li(Mn 0.5 Fe 0.5 ) 1-x V x The first cycle capacity of PO4 at 1C is 144 mAh g -1 The discharge capacity after 100 cycles is 137.1 mAh g -1 The capacity retention rate is 95.2%, which has a higher discharge specific capacity and better cycle performance; the electrochemical performance of Example 4 (x=0.5%) is reduced to a certain extent.
[0068] Figure 6 The rate performance curves of Examples 1 to 4 are shown in Table 1. The discharge capacity of Example 3 at 0.1C is close to 150 mAh g -1 , which is consistent with the cycle test results, and can maintain close to 130mAh g at 5C -1 When the doping amount is reduced, the discharge specific capacity of the materials in Examples 1 and 2 gradually decreases with the reduction of the vanadium doping amount. During the test, the capacity retention rate from 0.1C to 5C also decreases significantly (to 82% and 78%, respectively). When the doping amount exceeds x = 0.35%, the capacity of the material in Example 4 at 0.1C is only 138.2 mAh·g -1 , 118mAh·g at 5C -1 .
Claims
1. A method for preparing a vanadium-doped lithium manganese iron phosphate positive electrode material, characterized in that: The soluble reducing agent, iron source, manganese source, ammonium metavanadate, lithium source and phosphorus source are uniformly mixed, and a hydrothermal reaction is performed to obtain a lithium iron manganese phosphate precursor, which is then subjected to secondary hydrothermal reaction and then mixed with a carbon source and calcined to obtain vanadium-doped lithium iron manganese phosphate nanoparticles.
2. The preparation method according to claim 1, characterized in that: The hydrothermal synthesis temperature is 140°C-200°C, preferably 140°C-180°C, and the time is 4h-12h, preferably 4h-10h; The secondary hydrothermal synthesis temperature is 140-200°C, preferably 140-180°C, and the time is 0.5h-4h, preferably 0.5h-2h; the calcination temperature is 400-800°C, preferably 500-700°C, and the time is 6h-12h, preferably 6h-10h.
3. The preparation method according to claim 1, characterized in that: The soluble reducing agent includes: at least one of glucose, sucrose, and vitamin C; the iron source includes at least one of ferrous oxalate and ferrous sulfate; the manganese source includes at least one of manganese phosphate and manganese sulfate; the lithium source includes at least one of lithium hydroxide, lithium phosphate, lithium dihydrogen phosphate, and dilithium hydrogen phosphate; the phosphorus source includes at least one of phosphoric acid, lithium phosphate, lithium dihydrogen phosphate, or dilithium hydrogen phosphate; and the carbon source includes: at least one of ascorbic acid, glucose, and sucrose.
4. The preparation method according to claim 1, characterized in that: The molecular formula of vanadium-doped lithium manganese iron phosphate positive electrode material is Li(Mn 0.5 Fe 0.5 ) 1-x V x PO4; the mass of the carbon source added C accounts for 2wt%-10wt% of the vanadium-doped lithium manganese iron phosphate positive electrode material, preferably 2wt%-5wt%; the doping amount x of V is in the range of 0.1%-1%, preferably 0.25%-0.5%.
5. The preparation method according to claim 1, characterized in that: The hydrothermal solution medium is ethylene glycol, dimethyl sulfoxide or a mixed solution of ethylene glycol and water.
6. The preparation method according to claim 5, characterized in that: The solvent of the hydrothermal system includes a mixed solution of ethylene glycol and water, wherein the ratio of ethylene glycol to water is in the range of 1:3-3:1, and the preferred range is 1:2-2:1; the products after the two hydrothermal reactions are dried in a vacuum drying oven, the drying temperature range is 60°C-120°C, the preferred range is 80°C-100°C, and the drying time range is 12h-24h, and the preferred range is 18h-24h.
7. The preparation method according to claim 1, characterized in that: The short nanorod particles of lithium manganese iron phosphate grow directionally into nanoparticles with a length of less than 100 nm and a width of less than 20 nm.
8. Vanadium-doped lithium manganese iron phosphate positive electrode material prepared by the method according to any one of claims 1 to 7.
9. The use of the vanadium-doped lithium manganese iron phosphate positive electrode material according to claim 8, characterized in that: Used to prepare battery positive electrodes, especially lithium-ion battery positive electrodes.
10. A positive electrode of a battery or a lithium-ion battery, characterized in that: It is prepared from the vanadium-doped lithium manganese iron phosphate positive electrode material described in claim 8.
Citation Information
Patent Citations
Positive electrodematerial for lithium ion battery and preparation method thereof
CN108987747A
Preparation method of carbon quantum dot modified LiFePO4 positive electrode material
CN111525102A
Lithium iron phosphate, preparation method thereof, lithium ion battery and electric driving device
CN114314552A
Method for preparing carbon-coated lithium ferric manganese phosphate from rutile mother liquor and application of carbon-coated lithium ferric manganese phosphate
CN115799483A
Positive electrode active material and preparation method thereof, battery and electric device
CN116002651A
Cited By
Vanadium-doped lithium manganese iron phosphate positive electrode material and preparation method and application thereof
CN120237197A
Double-element doped high-manganese lithium iron manganese phosphate positive electrode material and preparation method thereof
CN121938898A